Perspectiva resignificada de la planeación como opción para el desarrollo. Análisis de caso (2010)
ABSTRACT: This paper focuses its attention on the research`s results “Planning as an option for development: A Contemporary Bet. Case study Participative Budget, 2004-2007, Comuna 1, Municipality of Medellín”, such research was done in the framework of a formative research process, by Social Workers of the Universidad de Antioquia. In this study a renewed perspective of planning for development is analyzed in depth which is also involved in contextual conditions as well as its materialization in a territory. The theoretical strengthening, in the development as well as in the planning, is proposed through contemporary authors who contribute to make clear new elements and associations that justify planning as an option for development. The case documentation: Participative Planning and Budget Program of the Comuna 1 of the Municipality of Medellín made possible to analyze it from the theoretical elements exposed, allowing the identification of some tensions and challenges that existing development projects currently face. Based on the involving of theory-praxis, methodological strategies are designed to guide planning processes for the territory development; leading to place it as a social intervention process. This contribution becomes a helpful path, for educational practices as well as Professional ones, in the Social Work and Human and Social Sciences.